Factors that contribute to awareness of halal logistics among muslims in the Klang Valley / Emi Normalina Omar ...[et al.] - Omar, Emi Normalina; Ramli, Ahmad Adeel; Jaafar, HarlinaSuzana; Abu Hassan, LailatulFaizah; Othman, Abdul Kadir; Ali, Husniyati (Faculty of Business and Management and UiTM Press Universiti Teknologi MARA, Malaysia., 2017)
The demand for Halal products is increasing tremendously not only from Muslim countries but also non-Muslim countries. The component of Halal industry can be classified into three areas, namely services, food and non-food. Halal logistics is categorized into the service component. Halal logistics covers warehousing, transportation and terminal operations. There are three principles of Halal logistics; avoiding direct contact with haram, addressing the risk of contamination, and perception of the Muslim consumer. For non-Muslim countries, the first two principles apply. Malaysia is regarded as a Muslim majority country; therefore, there is a need to explore the level of awareness on Halal logistics. This research paper aims to explore the level of awareness of the Muslim in the Klang Valley, Selangor. Data were collected through convenient sampling from 250 respondents and analyzed by using SPSS. The findings indicate that religious belief is a significant predictor of Halal logistics awareness among Muslims.